Sperm telomere length as a novel biomarker of male infertility and embryonic development: A systematic review and meta-analysis - Yuan, Yacheng; Tan, Yangyang; Qiu, Xiaolong; Luo, Hengfeng; Li, Yuxiang; Li, Ruijie; Yang, Xukai (Frontiers in Endocrinology, 2023)
Telomeres have an essential role in maintaining the integrity and stability of the human chromosomal genome and preserving essential DNA biological functions. Several articles have been published on the association of STL with male semen parameters and clinical pregnancy. The results, however, are either inconclusive or inconsistent. Therefore, the aim of this meta-analysis was to systematically assess the accuracy and clinical value of sperm telomere length (STL) as a new marker for diagnosing male infertility and predicting the quality of embryonic development. Overall, Twelve prospective observational cohort studies (1700 patients) were eligible for inclusion in the meta-analysis.The meta-analysis showed that there was a positive linear correlation between STL and semen parameters and the optimal cut-off value for STL diagnosing male infertility was 1.0, with a sensitivity and specificity of 80%. Regarding STL and embryonic development, the clinical pregnancy rate was associated with longer STL , and there was no significant difference between the two groups in terms of fertilisation rate . Our study showed that STL has good diagnostic and predictive value for male fertility and clinical pregnancy, and could be used as a new biomarker for diagnosing male infertility and predicting embryonic development.